#### Answer

$(n^{9})^{0}=1$

#### Work Step by Step

$(n^{9})^{?}=1$
The zero as an exponent rule states that for every nonzero number $a$, $a^0=1$.
We use this rule to rewrite the equation: $(n^{9})^{?}=n^0$
To raise a power to a power, we multiply the exponents. Therefore, in order for this equation to be correct, the product of $9$ and the second exponent must equal $0$. The only way this would work is if the second exponent is $0$ because $9\times0=0$.
Therefore, the correct equation is $(n^{9})^{0}=1$